The San Francisco Civic Center : A History of the Design, Controversies, and Realization of a City Beautiful Masterpiece - Haas, James W. (Book collections on Project MUSE., 2019)
"The first and only book available which describes the origins of American civic centers and then tells the history of the greatest of the them, the San Francisco Civic Center"--Provided by publisher.